Name Changes in Common Indian Plants - Raizada, M. B. (Indian Forester, 1958)
This paper embodies the results of 'research' spread over a period of several years and gives the up-to-date correct botanical names, in accordance with the latest International Code of Botanical Nomenclature, of about 815 common Indian plants. Immediately below the correct names are given important synonyms. Attempt has been made throughout to follow the Principle of Priority, which is of fundamental importance in Taxonomy. When a name other than the usual one has been adpoted, the basionym on which the new name is based has been invariably given. For the sake of convenience and facilitate reference the names have been arranged alphabetically and an index provided at the end so that workers acquainted with more familiar names, commonly in use at present, may be able to trace easily the correct names. The following 22 new combination have been made :- Argyreia atropurpurea (Wall. ) ; A.barbata ( Wall. ) ; A.bella ( Clarke) ; A.bracteosa (Clarke) ; A.confusa (Prain); A.hirsutissima (Wall.); A. longifolia (Coli. et Hemsl. ) ; A.mastersii ( Prain ) ; A.maymyo ( W. W. Smith); A.rubens (Wall. ) ; Bonamia elegans (Wall.); B. evolvuloides (Wight); Ecbotium viride (Forsk.) Alston var. dentata ( Clarke) ; E.viride ( Forsk. ) Alston var. latevirens ( Clarke) ; E. virid. ( Forsk. ) Alston var. rotundifolia ( Clarke) ; Grona simplidfolia ( Dalz.) ; Murdannia esculentum (Wall.); M.siennea (Blatter); M.terminalis (BI.); M.zeylanica ( CI. ) Bruck. var. longiscapa ( Clarke) ; Operculina petaloidea (Choisy) van Oosts. var. pauciflora ( Clarke) and Syzygium cerasoideum ( Roxb. ). Three new names have also been proposed : Garcinia talbotii for G.malabarica Talbot, Plectranthus beddomei for P.urticifolius Hk. f. and Commelina wightii for C.glabra (Wt.) Clarke, as they are pre-occupied by Garcinia malabarica Desr. ( 1789 ), P.urticifolius ( Lamk. ) Salisb. ( 1796) and C. glabra Meyer ( 1818) respectively and hence invalid according to rules.